Pengaruh Kepemimpinan Kepala Madrasah dan Motivasi Kerja Terhadap Kinerja Guru MTs Ma’arif NU Se-Kabupaten Banyumas Tahun Pelajaran 2014/2015 - Surip Riyadi (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
The quality of education in Indonesia is considered by many to be low, due to various kinds of problems ranging from internal madrasah problems to external madrasah problems, such as the weak leadership role of the madrasa head, teacher performance, student achievement, infrastructure, community environment, motivation and so on. Lots of problems that arise in the world of education. Therefore, it is necessary to do research on the problems that occur. Some problem factors that can be taken one of them is the influence of the leadership of the madrasah head and work motivation on the performance of MTs Ma'arif NU teachers in Banyumas Regency.In conducting the research, the researcher used quantitative research using a stratified random sampling technique, in which a portion of the population was selected from several strata or subgroups and separate samples were taken from each subgroup, with high, medium and low provisions. The number of respondents was 45 respondents / teachers at MTs Ma'arif NU in Banyumas Regency. The results of data collection showed that there was a significant influence between the leadership of the madrasah head and work motivation on the performance of MTs Ma'arif NU teachers in Banyumas Regency, both independently and together. The madrasa head leadership contributed 64.44%, the contribution of work motivation was 66.60%, and the joint contribution was 31.40%, while the rest were 35.56%, 33.40% and 68 respectively. 60% of the teacher performance at MTs Ma'arif NU which is influenced by other variables outside of this study. Suggestions that need to be considered are that the leadership of the madrasa head needs to be improved and positive work motivation must be maintained and developed so that the work performance of MTs Ma'arif NU teachers in carrying out their duties as educators (educators) can be carried out in accordance with the objectives of madrasah education